2017
DOI: 10.1167/17.13.2
|View full text |Cite
|
Sign up to set email alerts
|

Selective enhancement of orientation tuning before saccades

Abstract: Saccadic eye movements cause a rapid sweep of the visual image across the retina and bring the saccade's target into high-acuity foveal vision. Even before saccade onset, visual processing is selectively prioritized at the saccade target. To determine how this presaccadic attention shift exerts its influence on visual selection, we compare the dynamics of perceptual tuning curves before movement onset at the saccade target and in the opposite hemifield. Participants monitored a 30-Hz sequence of randomly orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 50 publications
4
75
1
Order By: Relevance
“…One interesting exception was the result that high SFs were more reliably identified during saccades than during fixation when the blanking period was introduced in Experiment 2. We speculate that this result is a consequence of well-established effects: During the preparation of a saccade, visuospatial attention selected the target of the movement Kowler, Anderson, Dosher, & Blaser, 1995;Ohl et al, 2017;Rolfs & Carrasco, 2012), increasing visual sensitivity for high SFs in an obligatory fashion (Li et al, 2016;Li, Pan, & Carrasco, 2019). In the context of our task, this increase in sensitivity at the saccade target could have led to two complementary phenomena.…”
Section: Distinct Motion Streaks Are Associated With High Task Performentioning
confidence: 68%
See 1 more Smart Citation
“…One interesting exception was the result that high SFs were more reliably identified during saccades than during fixation when the blanking period was introduced in Experiment 2. We speculate that this result is a consequence of well-established effects: During the preparation of a saccade, visuospatial attention selected the target of the movement Kowler, Anderson, Dosher, & Blaser, 1995;Ohl et al, 2017;Rolfs & Carrasco, 2012), increasing visual sensitivity for high SFs in an obligatory fashion (Li et al, 2016;Li, Pan, & Carrasco, 2019). In the context of our task, this increase in sensitivity at the saccade target could have led to two complementary phenomena.…”
Section: Distinct Motion Streaks Are Associated With High Task Performentioning
confidence: 68%
“…Each of these effects might have also contributed to the difference between saccade and replay conditions. Moreover, saccades lead to other changes, such as attention shifts (Rolfs, Jonikaitis, Deubel, & Cavanagh, 2011) or changes in perceptual tuning (Li et al, 2016;Ohl, Kuper, & Rolfs, 2017), that cannot be controlled for in a simulated saccade condition.…”
Section: Task Performance During Saccades and During Fixationmentioning
confidence: 99%
“…Previous psychophysical studies have shown that perceptual enhancement at the saccade target is at maximum immediately prior to saccade onset (Deubel, 2008;Li et al, 2016;Ohl et al, 2017;Rolfs & Carrasco, 2012;Rolfs et al, 2011). In these experiments, we focused on the Gaussian condition exclusively and pooled across foveal-motion and no-foveal-motion conditions as we found no significant differences between them during the early open-loop epoch in Experiment 1.…”
Section: Experiments 2 and 3: The Impact Of Timing Of Motion Integratmentioning
confidence: 95%
“…The orientation sensitivity and perceived contrast for targets immediately before saccades are increased (Rolfs & Carrasco, 2012). The tuning for stimulus orientation has also been found to sharpen specifically at the saccade target (Ohl, Kuper, & Rolfs, 2017), and there is an enhancement for high spatial frequency features (Li, Barbot, & Carrasco, 2016). The enhancement associated with presaccadic attention is involuntary and occurs even when contrary to task demands.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation